The "new stage" of Roma policy - a general survey of activities at international level concerning Roma issues - Polzer-Srienz, Mirjam (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The increased attention paid to Roma and Sinti issues at the national and international level in the last decade of the 20th century was an encouraging sign for the development of a clearer understanding of the complexities of policy issues related to Roma. Nevertheless, the numerous attempts of international and national policies to improve the status of Roma and Sinti don't seem to effect significantly the social, political and economic situation of Roma and Sinti. Political and institutional recognition of Roma is a precondition for still needed reinforced activities to combat prejudices,hostilities, discrimination and violence against Roma and Sinti and promotion of social integration. It seems that the Roma policy is developing to a systematic combination of the methods of the social approach, the implementation of minority rights and prevention of discrimination and violation. Despite the fact that systematic national strategies and action plans exist in SEE countries, measures taken often donćt have the desired effect. Nevertheless, one improvement that can be mentioned is the realization by the relevant policy makers that single activities without a long-range concept and without cooperation with Roma are not sufficient to secure the implementation of human and minority rights for Roma. Legislative measures alone are very important but still not enough to strengthen the situation of Roma. At the same time positive action and affirmative actions are not enough, if intensive cooperation between state authorities, civil society and the Roma population doesnćt exist. If states were to consider this then the new stage of Roma policy will have good chances to bring about some significant positive developments.
Keywords: Romi; etnične skupine; narodne manjšine; human rights; človekove pravice; pravno varstvo